Blockade of endothelin-1 receptor B regulates molecules of the major histocompatibility complex in sickle cell disease - Inostroza-Nieves, Yaritza; Rivera, Alicia; Romero, José R. (Frontiers in Immunology, 2023)
Molecules of the Major Histocompatibility Complex (MHC) have been proposed to lead to vaso-occlusive crises in Sickle Cell Disease (SCD). Endothelial cells express MHC molecules following exposure to cytokines. SCD is characterized, in part, by vascular endothelial cell activation, increased oxidative stress, sickle cell adhesion, and excess levels of endothelin-1 (ET-1). ET-1 activates endothelial cells, induces oxidative stress and inflammation, and regulates erythrocyte homeostasis. However, the role of ET-1 on MHC regulation in SCD is unclear. We first studied two sickle transgenic knockout mouse models of moderate to severe disease phenotype, βSAntilles and Berkeley (BERK) mice. We observed significant increases in MHC molecule, H2-Aa mRNA levels in spleens, lungs and kidneys from transgenic sickle mice when compared to transgenic knockout mice expressing human hemoglobin A (HbA). Mice treated for 14 days with ET-1 receptor antagonists had a significant reduction in H2-Aa mRNA. We characterized the effect of ET-1 on MHC class II expression in the human endothelial cell line EA.hy926. We observed dose-dependent increases in the expression of MHC class II (HLA-DR) and MHC transcription factor (CIITA) that were significantly blocked by BQ788, a selective blocker of ET-1 type B receptors. Chromatin immunoprecipitation studies in EA.hy926 cells showed that ET-1 increased Histone H3 acetylation of the promoter region of HLA-DRB; an event that was blocked by BQ788. These results implicate ET-1 as a novel regulator of MHC class II molecules and suggest that ET-1 receptor blockade represents a promising therapeutic approach to regulate both immune and vascular responses in SCD.